Exploration of biomarkers for inhibitor development in persons with hemophilia A - Meng-Ni Fan; Tangliang Shen; Barbara A. Konkle; Xiaohe Cai; Ting-Yen Chao; Marilyn Manco-Johnson; Anna V. Faino; Junping Zhang; Shumin Bao; Weidong Xiao; Lei Li; Carol H. Miao (Research and Practice in Thrombosis and Haemostasis)
Background: Inhibitor development remains a significant challenge for hemophilia A (HA) treatment. Cytokines and glycosylation play crucial roles in inducing and regulating immune responses. Cytokine and altered N-glycan profiles have the potential to be biomarkers in association with the presence of inhibitors in persons with HA. Objectives: We investigated the association of cytokine and plasma N-glycan profiles with inhibitor presence. Methods: In 60 persons with HA and 23 controls, we analyzed 10 cytokines and used multivariable regression to assess their association with inhibitor presence. Given the challenges of validating these findings in previously untreated patients, we employed an HA mouse model to explore the association between cytokine levels and inhibitors. We also examined the correlation between plasma N-glycan profiles and inhibitors in persons with HA, analyzing adult and pediatric groups separately due to age-dependent glycosylation. Results: Elevated granulocyte colony-stimulating factor and interleukin (IL) 6 levels, coupled with decreased IL-10, were significantly associated with inhibitor presence in multivariable regression analysis. High-titer inhibitor was observed in factor (F)VIII-treated mice experiencing chronic inflammation with increased levels of granulocyte colony-stimulating factor, IL-6, and macrophage inflammatory protein-1β, a murine IL-8 homolog, but not in those receiving FVIII alone, consistent with our clinical observations. Inhibitor-positive adult patients exhibited higher biantennary N-glycan and reduced multiantennary N-glycan ratios compared with inhibitor-negative adults. Conversely, inhibitor-positive pediatric patients displayed decreased sialic acid ratios. Conclusion: These findings highlight the association of inhibitor presence with altered plasma cytokine levels and N-glycosylation patterns. Prospective validation is crucial to confirm these associations, develop robust biomarkers, and improve inhibitor risk assessment for persons with HA.